Peran Komitmen Organisasi, Kepemimpinan, dan Budaya Organisasi Terhadap Peningkatan Kinerja Pegawai (Studi Kasus BPKAD Provinsi Papua Barat) - Peres Sefaniwi, Samuel; Lambi, Manuel (LPPM Universitas Ekasakti Padang, 2024)
This research aims to analyze: 1) The partial and simultaneous influence of organizational commitment, leadership and organizational culture on employee performance, 2) The most dominant variables that influence employee performance at BPKAD West Papua Province. The population of this study was 48 people. The sample was determined using a saturated sampling technique so that the entire population was sampled. Data collection uses questionnaires and documents, data analysis uses multiple linear regression. The research results show that: 1) Organizational Commitment, leadership and organizational culture have a partially positive and significant effect on employee performance, 2) Organizational commitment, leadership and organizational culture have a simultaneous positive and significant effect on employee performance, 3) Leadership is the most dominant variable influence on employee performance at BNPKAD West Papua Province. 4) The coefficient of determination results show a value of 89.8%, meaning that employee performance variables can be explained by the variables Organizational Commitment, Leadership and Organizational Culture, while the remaining 10.2% is explained by other variables outside the model.